1997
DOI: 10.1038/ng0197-30
|View full text |Cite|
|
Sign up to set email alerts
|

Mutations in human cause limb and cardiac malformation in Holt-Oram syndrome

Abstract: Holt-Oram syndrome is characterized by upper limb malformations and cardiac septation defects. Here, we demonstrate that mutations in the human TBX5 gene underlie this disorder. TBX5 was cloned from the disease locus on human chromosome 12q24.1 and identified as a member of the T-box transcription factor family. A nonsense mutation in TBX5 causes Holt-Oram syndrome in affected members of one family; a TBX5 missense mutation was identified in affected members of another. We conclude that TBX5 is critical for li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
306
0
4

Year Published

1998
1998
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 984 publications
(311 citation statements)
references
References 37 publications
1
306
0
4
Order By: Relevance
“…Figure 4 Continued family, retinoic acid receptor (RAR) family, retinoid-X-receptor (RXR) family, and of the T-box family] play important roles in limb development (Tickle & Eichele 1994;Martin 1998;Ohuchi et al 1998;Sekine et al 1999). Intriguingly, our observed phenotypes of mRor2 À/À mice are somewhat reminiscent of those of Holt±Oram syndrome, which is characterized by upper limb malformations and cardiac septation defects, in which the TBX5 gene is mutated (Basson et al 1997;Li et al 1997;Basson et al 1999). It has been reported that the TBX5 gene is expressed in the upper (fore) limbs and another T-box family gene, TBX4, is expressed dominantly in the lower (hind) limbs (Chapman et al 1996), and that TBX4 (and PITX1) and TBX5 determine the identities of the upper (fore) limbs (or wings) and lower (hind) limbs (or legs), respectively (Ohuchi et al 1998;Logan & Tabin 1999;Vogel 1999).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Figure 4 Continued family, retinoic acid receptor (RAR) family, retinoid-X-receptor (RXR) family, and of the T-box family] play important roles in limb development (Tickle & Eichele 1994;Martin 1998;Ohuchi et al 1998;Sekine et al 1999). Intriguingly, our observed phenotypes of mRor2 À/À mice are somewhat reminiscent of those of Holt±Oram syndrome, which is characterized by upper limb malformations and cardiac septation defects, in which the TBX5 gene is mutated (Basson et al 1997;Li et al 1997;Basson et al 1999). It has been reported that the TBX5 gene is expressed in the upper (fore) limbs and another T-box family gene, TBX4, is expressed dominantly in the lower (hind) limbs (Chapman et al 1996), and that TBX4 (and PITX1) and TBX5 determine the identities of the upper (fore) limbs (or wings) and lower (hind) limbs (or legs), respectively (Ohuchi et al 1998;Logan & Tabin 1999;Vogel 1999).…”
Section: Discussionmentioning
confidence: 65%
“…First, mRor2 is required for cardiac septal formation. Recent genetic analyses have revealed that many regulatory molecules, including growth factors, receptors and transcription factors, are involved in the development of the heart (Nagasawa et al 1996;Basson et al 1997;Li et al 1997;Tessarollo et al 1997;de la Pompa et al 1998;Ranger et al 1998;Schott et al 1998;Tachibana et al 1998; reviewed in Burn & Goodship 1996;Lyons 1996;Rossant 1996;Barinaga 1998), although in general their roles are not restricted to septal formation. Interestingly, defects of the cardiac septum have been, thus far, the major abnormality observed in the cardio-vascular system of mRor2 À/À mice.…”
Section: Discussionmentioning
confidence: 99%
“…In our patients the gene defect could have its major effect on the mesenchymal condensation process of the anterior (radial) part of the upper limb, comparable with the effects of the mutant TBX5 gene. 14,15 Haploinsufficiency of this gene causes mainly anterior limb malformations in patients with Holt-Oram syndrome, whereas haploinsufficiency of the TBX3 gene causes mainly posterior limb malformations in patients with the ulnar-mammary syndrome. 14,16 The gene defect could also be involved in differentiation or growth of the radius.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the studies have been focusing on the genetic study of this condition, associating the morphological abnormalities with a mutation on an autosomal dominant gene (TBX5), which resides on the long arm of the chromosome 12q24.1 3 . Until now, the correlation between the severity of the upper limb abnormalities and the cardiac abnormalities could not be established 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Holt-Oram syndrome is an autosomal dominant disorder, caused by mutations on chromosome 12q24.1 3 that inactivate the TBX5 gene. The criteria for diagnosing this syndrome include abnormalities of the thumb (triphalangia, hypoplasia or aplasia) and congenital heart disease.…”
mentioning
confidence: 99%